Management of Clevudine-Resistant Chronic Hepatitis B: A Multicenter Cohort Study - Cho, Eun Young (Gut Liver, 2017)
BACKGROUND/AIMS: Data are lacking regarding the management of chronic hepatitis B (CHB) with resistance to clevudine (CLV). This study evaluated the efficacy of different rescue therapies for CLV-resistant CHB. METHODS: Patients with CLV-resistant CHB were enrolled in the cohort, and all patients developed virologic breakthrough during CLV therapy and had confirmed-genotypic resistance to CLV (rtM204I mutation) before enrollment. RESULTS: Of the 107 patients, 12 received adefovir (ADV), 21 received a CLV plus ADV combination (CLV+ADV), 34 received a lamivudine plus ADV combination (LAM+ADV), and 40 received entecavir (ETV) therapy for 48 weeks. The CLV+ADV group had the lowest hepatitis B virus (HBV) DNA level (p<0.0001) and showed the greatest reduction of HBV DNA levels from baseline compared to all other groups (p=0.004) at week 48. HBV DNA was undetectable (<70 IU/mL) in 0%, 57.1%, 21.2%, and 27.5% (p=0.003) of the patients in each group, respectively, at week 48. At the end of the study, the mean alanine transaminase (ALT) level, rate of ALT normalization, and rate of hepatitis B envelope antigen loss or seroconversion did not differ between groups. CONCLUSIONS: CLV+ADV combination therapy in patients with CLV-resistant CHB more effectively suppresses HBV replication than ETV, ADV, or LAM+ADV therapy.